Prevalência da infecção pelo eritrovírus B19 e associações clínicas em crianças com anemia falciforme provenientes da triagem neonatal e acompanhadas no Hemocentro de BeloHorizonte (MG) - Marina dos Santos Brito Silva Furtado (2012)
Introduction: The human erythrovirus B19 (B19V) causes significant morbidity in children with sickle cell anemia, but there are few studies on the epidemiology of B19V infection in this population, especially in Brazil. The virus has tropism for erythroblasts causing apoptosis, which in patients with chronic hemolytic anemia can lead to a transient bone marrow aplasia, which is characterized by a temporary halt in erythropoiesis, with a sharp drop in hemoglobin concentration and reticulocyte count. Objectives and methods: The aim of this study was to estimate the prevalence and incidence of infection with erythrovirus B19 in children with sickle cell disease screened by the Newborn Screening Program of Minas Gerais and followed at Blood Center of Belo Horizonte, Hemominas Foundation. Samples from 239 patients were tested using ELISA (Biotrin, Dublin, Ireland) for detection of IgG and IgM anti-B19V, and with a standardized assay for real-time PCR using SYBR Green for detection of viral DNA. The positive DNA samples were also tested using hydrolysis probes (TaqMan) for identification of virus genotype. Results: The median age of the children tested was 5.8 years. Of these, 10.9% (26/239) presented current or recent infection characterized as follows: six (2.5%) positive only for the viral DNA, 2 (0.8%) positive only for IgM, 1 (0, 4%) positive for IgM and DNA, 16 (6.7%) positive for viral DNA and IgG, and only 1 (0.4%) positive for viral DNA, IgG, and IgM. We identified 37 (15.5%) individuals positive only for IgG, featuring a profile of past infection. More than 70% (176/239) presented negative serological and molecular results for B19V and from this group 51 children had a second sample withdrawn at a mean interval of one year. Conversion of negative to positive serological and/or molecular status was detected in 14 incident cases (27, 5%). Of the 45 positive samples tested using molecular SYBR Green, 32 were confirmed positive by the TaqMan system. Genotype 1 infection was present in all positive DNA samples, except for one, in which there was a co-infection by genotypes 1 and 3. The analysis of clinical and hematological data showed an association of B19V infection with transient aplastic crisis, higher number of transfusions, and higher rate of hospital admissions. It was also observed that the higher the child's age, the higher the probability of B19 infection. Conclusions: The findings in this study allowed us to estimate a prevalence of 26.4% and an incidence of 29.1 cases/100 patient-years for B19V infection in this population. B19 infection is thus common in children with sickle cell disease in Belo Horizonte and, as expected, is associated the with transient bone marrow aplasia. The association of the infection with high frequency of hospital admissions also indicates that viral infection can lead to worsening of sickle cell manifestations. It is possible that virus transmission has occurred through blood transfusion but the study design is inadequate to demonstrate it. Serological and molecular tests should be performed together, whenever possible, in order to increase the efficacy of the infection diagnosis.